The essential friends of libraries : fast facts, forms, and tips - Dolnick, Sandy (American Library Association, 2005)
Developed out of the questions that regularly come into Friends of Libraries U.S.A's (FOLUSA) main desk, this comprehensive, accessible resource is a one-stop treasure trove of information about the organization, personnel, finances, fund-raising, programs, and legal aspects of Friends groups.